The Effect of Taxpayer Compliance, Tax Audit and Tax Collection on Tax Revenue - Nur Anita Chandra Putry; Dina Oktarina (Universitas Muhammadiyah Makassar, 2022)
This study aims to test whether taxpayer compliance, tax audit and tax collection have an effect on tax revenue. The population in this study were individual taxpayers on the island of Belitung with a sample size of 115 respondents. The sampling technique for the respondents in this study used a non-probability sampling with a purposive sampling technique. Data collection was carried out by distributing questionnaires in the form of google form to respondents via social media such as WhatsApp and Facebook. Data were analyzed by multiple linear regression analysis using SPSS version 21 program. The results of this study indicate that taxpayer compliance, tax audit and tax collection have a positive and significant effect on tax revenue